The impact of a sound solid waste management system towards quality of life - Zainal, Mhd Saiful Anuar; Abdullah, Othman Yeop (Universiti Teknologi MARA, Kelantan, 2018)
A sound solid waste management system is a mandatory requirement to acquire for a good quality of life. It is a basic human’s need as well as a basic human’s right to ensure a clean and healthy environment to live in. This phenomenon makes the solid waste management system is an inevitable utility service underpinning the 21st century. It is important to note that the cost of being ignorance on the importance of cleanliness exceeds the financial cost per capita by a factor of 5 – 10 times over the proper system. In Malaysia, the generation of solid waste has increased for more than 91% over the past decade and it has reached 37,000 tons per day in 2016 whereby only 21% were recycled. The remaining waste were disposed without proper treatment at the disposal sites which are mostly dumpsites. The unavailability of proper treatment and disposal have led to severe pollutions which are very detrimental to the environment and the public health. These adverse impacts coupled with a substantial cost of RM2.3 billion spent in 2016 proved that the current practice of a Linear Economy of extract-make-use-dispose is not sustainable. This phenomenon has alarmed the government to immediately transform to a new system of a Resource Management within a Circular Economy which is based on a closed loop system that promotes the application of Reduce, Re-use and Recycle (3R) to minimize the waste generation while maximizing the resource yields by circulating the materials in use as efficiently as possible. Circular Economy is a proven concept to holistically resolve the very unique solid waste management issues which will ultimately improve the quality of life. This paper gives an insight into possibility of embracing the concept of Circular Economy to promote inclusivity at every layers of societies and to transform towards a zero waste society.